The use of Cr (CO)6 as an alternative CO source in Pd‐catalyzed C‐N bond formation: Synthesis of benzamides. (18th June 2019) - Mozaffari, Mozhdeh; Nowrouzi, Najmeh; Abbasi, Mohammad
Abstract : An efficient strategy for the synthesis of benzamides from acetamides and aryl iodides using 1 mol% Pd (OAc)2 as catalyst and Cr (CO)6 as CO‐precursor is described. This new synthetic methodology displays high functional group tolerance on both substrates and avoids the need for ligands, reducing agents, or other additives. The corresponding products were obtained in good to excellent yields at atmospheric pressure under mild reaction conditions. Abstract : Synthesis of benzamides from acetamides and aryl iodides using Pd (OAc)2 as catalyst and Cr (CO)6 as CO‐precursor.